PENGARUH EARNING DAN RISK PROFILE TERHADAP NILAI PERUSAHAAN PERBANKAN BUMN PERIODE 2018–2021 - Hasbullah A Arief Madani; Nurhayati; Gazali; Fadali Rahman (Faculty of Economics and Business, Universitas Warmadewa, 2026)
This study aims to analyze the effect of earnings (measured by Net Interest Margin/NIM) and risk profile (measured by Non-Performing Loans/NPL) on the firm value of state-owned banks for the 2018–2021 period. The research method used a quantitative approach with secondary data obtained from annual reports and financial statements of state-owned banks listed on the Indonesia Stock Exchange. The sample was selected using purposive sampling and analyzed using multiple linear regression. The results show that earnings have no significant effect on firm value. Conversely, risk profile has a negative but insignificant effect on firm value. These findings indicate that investors consider external factors and macroeconomic signals more than internal indicators of state-owned banks when assessing firm value.